A Study of Adjustment of High School students in Relation to Their Achievement, Sex and Locality (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2012)
Life is a continuous process of adjustment. Everyone is confronted with the problem of adjustment If we examine the various activities of mans life, It is obvious that most of them involve adjustment of the individual of his vocational, social and economic problems. The process of adjustment starts right from the birth of the child and continuous till his death.